The Use Of Portable Ultrasound By Paramedics In The Prehospital Setting For Rapid Trauma Assessment And Its Impact On Diagnosis And Patient Outcomes (The Review of Diabetic Studies, 2025)
Trauma remains a leading cause of preventable death worldwide, emphasizing the critical need for rapid and accurate prehospital assessment. Recent technological advances have enabled paramedics to utilize portable ultrasound—commonly known as point-of-care ultrasound (POCUS)—to identify life-threatening conditions such as internal bleeding, pneumothorax, and cardiac tamponade before hospital arrival. This systematic review examines the use of portable ultrasound by paramedics in the prehospital setting for rapid trauma assessment and its impact on diagnostic accuracy, triage decisions, and patient outcomes. Literature published from 2016 to 2025 was systematically analyzed across major databases, including PubMed, Scopus, and CINAHL. The evidence demonstrates that paramedics can perform focused assessment with sonography for trauma (FAST) or extended FAST (eFAST) with high feasibility and diagnostic accuracy after structured training. Studies reported reduced scene and transfer times, improved triage to appropriate trauma centers, and enhanced communication with receiving hospitals. However, robust evidence linking prehospital ultrasound use to improved morbidity and mortality remains limited. Further large-scale trials and standardized training frameworks are essential to validate its impact on outcomes and system efficiency. Overall, portable ultrasound represents a transformative tool in prehospital trauma care, enhancing early diagnosis and supporting data-driven clinical decisions by paramedics.